FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG - Nurkhasanah, Fitri Laili; Purbasari, Heppy (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Submission of financial reports must be reported to the public as quickly as possible and for several public companies in Indonesia this is still a problem every year.This research aims to identify the influence of audit tenure, size of the public accounting firm (KAP), and auditor industry specialization on audit report lag. The independent variables in this research are audit tenure, the size of the public accounting firm (KAP), and auditor industry specialization. The dependent variable in this research is audit report lag. The population in this study are LQ-45 companies listed on the Indonesia Stock Exchange (BEI) during 2019-2021. The research period was carried out for 3 years. The sampling technique used was purposive sampling with a sample of 84 companies. The analytical method of this research uses multiple linear regression with the help of SPSS 26. The results of this research prove that partial audit tenure has no effect on audit report lag, the size of the public accounting firm has no effect on audit report lag, and the auditor's industry specialization has an effect on audit report lag.